2001
DOI: 10.1007/pl00000901
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of cytokines in invertebrates

Abstract: Based on the assumption that invertebrates, like vertebrates, possess factors regulating responses to infection or wounding, studies dealing with the evolution of immunity have focussed on the isolation and characterisation of putative cytokine-related molecules from invertebrates. Until recently, most of our knowledge of cytokine- and cytokine receptor-like molecules in invertebrates relies on functional assays and similarities at the physicochemical level. As such, a phylogenetic relationship between inverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0
8

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 130 publications
(156 reference statements)
0
60
0
8
Order By: Relevance
“…Beyond the specific TNF ligand-receptor pathway, the general existence of cytokines in invertebrates has been argued to be the result of convergent evolution (30)(31)(32). For example, in D. melangastor, the Toll-like receptor pathway is involved in the response to microbial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the specific TNF ligand-receptor pathway, the general existence of cytokines in invertebrates has been argued to be the result of convergent evolution (30)(31)(32). For example, in D. melangastor, the Toll-like receptor pathway is involved in the response to microbial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In ascidians, the innate immune responses include cytokine-like humoral molecules and functional analogs of vertebrate inflammatory cytokines, including TNFα (Beschin et al 2001;Beck 1998). We have cloned and sequenced, for the first time, a TNFα-like cDNA from Ciona intestinalis (CiTNFα-like) challenged in vivo with LPS, a potent stimulator of proinflammatory cytokines, and have shown that the time-course of expression of the CiTNFα-like gene is modulated by the challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Hemocytes are protagonists of ascidian immunity (Parrinello 1996;Pinto et al 2003;Parrinello et al 2007;Vizzini et al 2008;Ballarin et al 2001), and ascidian cytokine-like molecules have been revealed by immunological (antibodies against heterologous cytokines) and biochemical methods. Humoral factors named "tunicate-cytokines" stimulate cell proliferation and modulate hemocyte phagocytosis activity or opsonized yeast (see Beschin et al 2001;Parrinello et al 2007). Recent progress in the genome sequencing of Ciona intestinalis has led to the development of an important tool for examining gene function and expression in immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the need for regulation of cellular immunity, as well as of hemopoietic development, has led to an intense search for invertebrate cytokines during the past decades. Functional homologues to vertebrate cytokines have been described mainly based upon immunocytochemical methods showing cross-reactivity of invertebrate cytokine-like molecules with Abs against vertebrate cytokines (6). Recent progress in genome-wide sequence analysis has enabled more detailed information on immune-related genes in invertebrates.…”
mentioning
confidence: 99%